Engineering performance of sustainable geopolymer foamed and non-foamed concretes. (17th January 2022) - Alnahhal, Ahmed Mahmoud; Alengaram, U. Johnson; Yusoff, Sumiani; Darvish, Pouya; Srinivas, Karthick; Sumesh, M.
Graphical abstract: Highlights: Compressive strength of geopolymer foamed concrete with 30% POFA was higher than control. Unreacted FA particles were found in the geopolymer foamed concrete. Pore diameters for geopolymer mortar vary between 0.43 and 15 µm. Si-O-Si bond was found stronger than the Al-O-Al bond. Abstract: This study investigates the effect of using palm oil fuel ash (POFA) as a partial replacement for fly ash (FA) in lightweight geopolymer foamed concrete and geopolymer mortar. Three different proportions of POFA contents of 10%, 20%, and 30% with a target fresh density of about 1300 ± 50 kg/m 3, were used. The development of compressive strength and splitting tensile strength were investigated over a 28-day curing period. Transport properties, in terms of water absorption, porosity, and sorptivity, were also investigated. Microstructural characteristics through XRD, SEM and EDX were also investigated and reported. The results found that the compressive strength of geopolymer foamed concrete, with up to 30% POFA, was higher than the control; however, for the POFA-based geopolymer mortar, the compressive strength reduced with increasing POFA content. The highest compressive strength of 6.1 MPa was recorded in the geopolymer foamed concrete with 20% POFA, whereas the control mix of geopolymer mortar produced 36.6 MPa. The geopolymer foamed concrete achieved 70% of its 28-day compressive strength within 3 days. The oven-dry density of the geopolymer foamed concrete ranged from 1193-1344 kg/m 3 . The ultrasonic pulse velocity (UPV) value was 1.5 km/s for the geopolymer foamed concrete while the geopolymer mortar had the range of 2.2–2.4 km/s. In general, the transport properties were mostly dependent on the oven-dry density of the geopolymer foamed concrete. The POFA content of 20% was found to provide the required silica and alumina to produce geopolymerization gel. Further, the SEM images showed unreacted FA particles that led to an increase in the voids. Furthermore, the XRD patterns showed the addition of foam affected the intensity of the peaks.